2007
DOI: 10.1089/vbz.2007.0104
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Q Fever Associated with a Horse-Boarding Ranch, Colorado, 2005

Abstract: Coxiella burnetii is a bacterium located worldwide that can cause Q fever when inhaled. We describe an outbreak of Q fever associated with a horse-boarding ranch that had acquired two herds of goats. We conducted case finding and cohort studies among persons who boarded horses on the ranch and ranchers and among residents in the surrounding community, and conducted sampling of the goats and environment, to determine risk factors for infection and guide public health interventions. Sixty-six ranchers and person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…The three other studies reported the presence of C. burnetii DNA in dust (17) or primarily soil samples from a geographically large area in the United States (11,14). The latter three studies investigated the presence of C. burnetii DNA in soil samples (6) and surface swabs (1,9) in relation to human Q fever outbreaks.…”
mentioning
confidence: 99%
“…The three other studies reported the presence of C. burnetii DNA in dust (17) or primarily soil samples from a geographically large area in the United States (11,14). The latter three studies investigated the presence of C. burnetii DNA in soil samples (6) and surface swabs (1,9) in relation to human Q fever outbreaks.…”
mentioning
confidence: 99%
“…Chronic Q fever usually presents as a culture-negative endocarditis. Recent outbreaks of Q fever have been associated with exposure to C. burnetii via inhalation of aerosolized bacteria from infected livestock (cows, sheep, or goats) (1,14,15). C. burnetii can replicate to high levels in the placentas of infected animals and is an established endemic abortifacient in goats and sheep (2,9).…”
mentioning
confidence: 99%
“…The presence of C. burnetii in herds of livestock and the known association of animal contact with human exposure (2,5,24,27) raise the possibility that the numbers of livestock at a given site could influence the ability to find Coxiella-positive samples. To investigate this possibility, the percentage of positive samples at each site was compared to the density of cows and sheep at each site.…”
Section: Resultsmentioning
confidence: 99%
“…The locations that contained C. burnetii DNA were quite diverse. The presence of C. burnetii in domesticated animal populations has been well established (2,5,10,24,27), so it is not surprising that C. burnetii DNA was found at dairy farms, cattle feed lots, veterinary hospitals, and goat-breeding facilities. However, many samples positive for C. burnetii DNA were collected from locations that had no livestock present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation